Antecedents of Smartwatch Purchase Intention in Indonesia - Ken Achmad Amran Prastanto; Arnolt Kristian Pakpahan (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
Rapid advances in digital technology and growing health awareness have contributed to the expansion of the wearable-device market, particularly the smartwatch market, in Indonesia. Smartwatches have evolved from simple accessories into multifunctional devices that support health monitoring, daily activities, communication, and productivity. This increasingly competitive market requires companies to understand the factors that influence consumers’ purchase intentions. This study examines the effects of electronic word of mouth (eWOM) on perceived value and customer attitude and investigates their subsequent effects on consumers’ purchase intentions toward smartwatches in Indonesia. A quantitative survey design was employed. Data were collected through an online questionnaire administered to 200 respondents who had knowledge of, experience with, or an interest in smartwatch products. Respondents were selected using nonprobability sampling with a purposive sampling technique. The data were analyzed using structural equation modeling with AMOS. The findings indicate that eWOM has positive and significant effects on both perceived value and customer attitude. Perceived value also has a positive and significant effect on customer attitude; however, its direct effect on purchase intention is not statistically significant. Customer attitude has a positive and significant effect on purchase intention. These findings demonstrate that online reviews, recommendations, and digitally disseminated information play an important role in shaping consumers’ value perceptions and attitudes toward smartwatches, which subsequently strengthen their purchase intentions. This study contributes to the consumer behavior and digital marketing literature by clarifying the role of eWOM, perceived value, and customer attitude in smartwatch purchase decisions. Practically, the findings provide insights for smartwatch companies seeking to develop effective digital marketing strategies in Indonesia.